(NwSTUP DO F)QÆLOSOFÆÇ (B((NSTISLIJ WIKLAD(B) :s)E (NNAW^ALXNIJ POS)QÆBNIK (B/s)E - (N}ERBA(B, (Ns(B. (Np(B.,s; (NzAGLADA(B, (No(B. (Na(B.s; (NtOFTUL(B, (Nm(B. (Ng(B.s; (N}EDR)QÆN(B, (Nw(B. (Nk(B.s)E; (N}ERBA(B, (Ns(B. (Np(B.,s ((NkI)QÇW (B:s)E (Nmaup(B,s, 2002)
(Nu POS)QÆBNIKU ROZGLQNUTO OSNOWNÆ [KOLI J TENDENCÆÇ SWÆTOWOÇ TA WÆT^IZNQNOÇ FÆLOSOFSXKOÇ DUMKI(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (Nf)QÆLOSOFÆQs)E -- (NsUTN)QÆSTXs)E -- (NpREDMETs -- (NmETODIs; (NF)QÆLOSOFÆQ sEREDNXOWÆ^^Qs)E; (Nw)QÆDRODVENNQs)E; (NF)QÆSOFÆQ KRAÇN sHODUs)E; )Qæ(NNDÆÇs)E; (NgREC)QÆÇs)E; (NONTOLOG)QÆQs)E; (NGNOSEOLOG)QÆQs)E; (Nl(B.(NfEJ)QÃRBAHs)E; (Ng(B. (NgEGELXs; (NkANT )Qæ(B.s)E; (NRELEG)QÆJNA FÆLOSOFÆQs)E